Morphology and electrical properties of polylactide / natural rubber blend filled with conductive nano carbon - Buys, Yose Fachmi; Anuar, Hazleen (2018)
Polylactide (PLA) is a biodegradable polymer that has potential to replace petroleum based polymers which currently used in conductive polymer composite (CPC). In order to develop environmentally friendly conductive polymer composites, in this research PLA was melt blended with natural rubber (NR), with addition of carbon black (CB) as the conductive filler. Miscibility of PLA/NR blends, dispersion states of CB in the blends, as well as electrical properties of the composites were evaluated. It was found that the PLA/NR blends were immiscible, and the sea island and co-continuous morphological structures were observed at PLA/NR with ratio of 80/20 vol% and 60/40 vol% respectively. Addition of CB to 60/40 PLA/NR matrix, brought the composites to become electrically conductive at CB content of 2 phr. It was also found that the impact strength of PLA/NR/CB composite is better than that of the neat PLA.